The impact of varying intensities of magnetically treated water on renal and testicular tissue - Alsaffar, Sura Fouad; Fadhil, Lamyaa Abdulridha; Baker, Ishraq Mohammed (Medicni Perspektivi, 2025)
This study aimed to investigate the effect of water treated with a magnetic field with different induction on the histological structure of the kidney and testicular tissue of albino rats. For this purpose, fifty albino rats were divided into five equal groups, the first of which was used as a control group, drank clean tap water for four weeks, the other groups were given daily water treated with a magnetic field with an induction of 500, 1000, 1500 and 2000 gauss. Then the animals were sacrificed and histological changes in the kidneys and testicles were examined. Histopathological examination of the kidneys of animals that were given water treated with a magnetic field with an induction of 500, 1000 and 1500 gauss revealed normal renal tubules and glomeruli. Histopathological examination of the kidneys of rats that consumed water treated with a magnetic field with an induction of 2000 gauss showed numerous focal hemorrhages and vacuolar degeneration of the epithelium lining the tubules. Histological sections at magnification revealed vacuolar degeneration of the epithelium of the tubules, mainly the collecting tubules, the formation of tubular casts and tubular necrosis. Examination of the testicular tissue of rats exposed to water treated with a magnetic field with an induction of 500 and 1000 gauss showed normal seminiferous structure and cytoarchitecture of the germinal epithelium areas, as well as normal interstitial tissue. In contrast, rats given water treated with a magnetic field with an induction of 1500 gauss showed marked narrowing of the seminiferous tubules, moderate vacuolar degeneration of the germinal epithelium, necrosis of a number of spermatogonia cells, and thickening of the testicular interstitium. Histopathological examination of the testes of rats exposed to water treated with a magnetic field with an induction of 2000 gauss showed significant vacuolar degeneration, necrosis of a number of spermatogonia cells, and thickening of the testicular interstitium, as well as significant damage to the seminiferous tubules and germinal epithelium. Thus, water treated with a magnetic field with an induction of 2000 gauss negatively affected both the kidneys and testicles, while water treated with a magnetic field with strength of 1000 gauss improved the function of the kidney and testicular tissue of rats and did not affect their structure.